Longitudinal Point Prevalence Survey of Antimicrobial Consumption in Russian Hospitals: Results of the Global-PPS Project - Svetlana Rachina; Yuliya Belkova; Roman Kozlov; Ann Versporten; Ines Pauwels; Herman Goossens; Elena Bochanova; Olga Domanskaya; Elena Elokhina; Ludmila Ezhova; Vladimir Mishchenko; Oksana Ni; et al. (MDPI AG, 2020)
Antimicrobial resistance is one of the key issues limiting the successful treatment of infectious diseases and associated with adverse medical, social and economic consequences on a global scale. The present study aims to evaluate antimicrobials prescribing patterns and assess progress in quality indicators in Russian multidisciplinary hospitals using three repetitive point prevalence studies (PPSs) over 4 years (Global-PPS 2015, 2017 and 2018). Out of 13,595 patients from 21 hospitals surveyed over the three time points, 3542 (26.14%) received antimicrobials, predominantly third-generation cephalosporins (44.7% in 2015, 34.1% in 2017 and 41.8% in 2018). Compliance with the hospital antibiotic guidelines was 74.8%, 66.8% and 74.3%, respectively. Indication for treatment was recorded in 72.6%, 84.1% and 82.6%, while stop/review date was documented only in 40.5%, 46.5% and 61.1% of cases. Perioperative antibiotic prophylaxis exceeded 1 day in 92%, 84% and 81% of cases. Targeted therapy rate at all time points did not exceed 15.1%, treatment based on the biomarkers rate-19.9%. For the part of PPS-2017 and 2018 analyzed in dynamics, no prominent trends were noted. The results of the project provide the basis for the development of appropriate antimicrobial stewardship programs tailored according to local practices for each hospital in the project.